Risk Factors of Anaemia among Children under Five Years in the Hohoe Municipality, Ghana: A Case Control Study. (25th June 2019) - Parbey, Phyllis Atta; Tarkang, Elvis; Manu, Emmanuel; Amu, Hubert; Ayanore, Martin Amogre; Aku, Fortress Yayra; Ziema, Sorengmen Amos; Bosoka, Samuel Adolf; Adjuik, Martin; Kweku, Margaret
Abstract : Background . Anaemia is one of the major causes of death among children under five years in Ghana. We examined the risk factors of anaemia among children under five years in the Hohoe Municipality, Ghana. Methods . This facility-based matched case control study recruited 210 children (70 cases and 140 controls) aged 6 to 59 months. Stratified and simple random sampling techniques were used to select mothers attending Child Welfare Clinic (CWC) for the screening of their children. Data were collected using a semistructured questionnaire. Finger prick blood was collected to estimate the haemoglobin (Hb) level and thick film was prepared to determine malaria parasitaemia. Axillary temperature was measured using an +electronic thermometer and anthropometric measurements were done using a weighing scale and inelastic tape measure. Continuous variables were presented as means and standard deviations and categorical variables as frequencies and proportions. Conditional logistic regression was used to determine the strength of association between the dependent and the independent variables. Statistical significance was considered at p value of <0.05. Results . The prevalence of anaemia was high (53.8%), while children whose mothers received iron supplementation during pregnancy were 7.64 times more likely to be anaemic compared with those who did not [AOR=7.64 (95% CI:1.41-41.20.93); p=0.018]. Children with poor dietary diversity were 9.15 times more likely to have anaemia [AOR=9.15 (95% CI: 3.13-26.82); p< 0.001]; and children whose mothers were farmers and traders were 83% [AOR = 0.17 (95% CI: 0.05-0.60); p=0.006] and 79% [AOR=0.21 (95% CI: 0.06-0.74); p=0.014], respectively, less likely to have anaemia. Conclusion . The biologic, intermediate, and underlying factors that were significantly associated with anaemia comprised maternal iron supplementation, poor dietary diversity, farmers, and traders. Given that iron supplementation during pregnancy did not protect children against anaemia, we recommend the child's nutritional dietary diversity is encouraged.